On behavioural synchronization in net systems - Thanh, Hoang Chi (Journal of Computer Science and Cybernetics, 2016)
In this paper we define a new operation on Net systems. The operation is compositional with respect to two distinct semantics – interleaving based on firing sequences and non-interleaving based on traces.